2022
DOI: 10.1038/s41366-022-01071-w
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat inflammation and fat embolism are associated with lung’s lipidic hyaline membranes in subjects with COVID-19

Abstract: Background Preliminary data suggested that fat embolism could explain the importance of visceral obesity as a critical determinant of coronavirus disease-2019 (COVID-19). Methods We performed a comprehensive histomorphologic analysis of autoptic visceral adipose tissue (VAT), lungs and livers of 19 subjects with COVID-19 (COVID-19+), and 23 people without COVID-19 (controls). Human adipocytes (hMADS) infected with SARS-CoV-2 were also studied. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
3
16
1
1
Order By: Relevance
“…In patients who died from COVID-19, a higher prevalence of CD68-positive M1 macrophages in visceral adipose tissue was observed compared to control patients without COVID-19. As expected, these were accompanied by crown-like structures, signs of adipocyte stress and death [46]. Previously, obesity was shown to increase the duration of type A influenza virus shedding in adults, whereas this was not the case for type B influenza [53].…”
Section: Mechanisms Responsible For An Increased Risk Of Severe Covid...supporting
confidence: 67%
See 1 more Smart Citation
“…In patients who died from COVID-19, a higher prevalence of CD68-positive M1 macrophages in visceral adipose tissue was observed compared to control patients without COVID-19. As expected, these were accompanied by crown-like structures, signs of adipocyte stress and death [46]. Previously, obesity was shown to increase the duration of type A influenza virus shedding in adults, whereas this was not the case for type B influenza [53].…”
Section: Mechanisms Responsible For An Increased Risk Of Severe Covid...supporting
confidence: 67%
“…blood hypercoagulability [44], and vitamin D deficiency [45], which are furthermore all risk factors for COVID-19 severity [46].…”
Section: Mechanisms Responsible For An Increased Risk Of Severe Covid...mentioning
confidence: 99%
“…Similarly, there is evidence that dysfunctional adipose tissue and systemic inflammation induced by obesity can contribute to airway inflammation and pulmonary disease [17]. In this context, several studies have shown that pulmonary dysfunction and metabolic disorders in patients with COVID-19 were directly correlated with excess VAT mass [89,90]; in contrast, an inverse correlation was observed with the adiponectin/leptin serum ratio [91]. These findings suggest that an altered adipokine-secretion profile from dysfunctional VAT in obese subjects could promote lung function decline in patients with COVID-19.…”
Section: Leptin Adiponectin and Pulmonary Dysfunctionmentioning
confidence: 99%
“…A systematic review of 60 consecutive forensic and 42 clinical COVID-19 post-mortem cases (>100 autopsies) reported that the major cause of diffuse alveolar damage is an immuno-thrombotic and thromboembolic mechanism driven by SARS-CoV-2-mediated inflammation [ 77 , 82 ]. The recent evidence by Colleluori et al on post-mortem COVID-19 cases assessed that using NSAIDs is paramount to addressing COVID-19 as early as possible, as the inflammation-driven machinery leads to lung fat embolism, causing an unfavorable prognosis of severely affected COVID-19 patients [ 83 ].…”
Section: Before Going To Hospitals: How Can Positive Patients Residen...mentioning
confidence: 99%